MATLAB/FLUENT Model for Studying the Uncertainty Quantification of Spent Nuclear Fuel Heat Transfer. (3rd July 2019) - Khalil, Imane; Pratt, Quinn
Abstract: A MATLAB tool that combines computational fluid dynamics with uncertainty quantification (UQ) applied to a two-dimensional FLUENT computational model to predict the heat transfer and the maximum temperature inside a spent fuel assembly is presented in this technical note. The tool is used to establish a connection between MATLAB and ANSYS-FLUENT for the purpose of UQ using the Sandia National Laboratory's UQ Toolkit. This tool allows users to adapt the UQ methodology to existing ANSYS-FLUENT models in order to automate the quadrature-based simulation process. The novelty of the tool presented in this technical note is its ability to generate results covering a continuous range of input parameters by using polynomial chaos expansions for the representation of random variables and the propagation of uncertainty in computational models.